2018
DOI: 10.1038/s41385-018-0004-9
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine-induced antigen-specific regulatory T cells attenuate the antiviral immunity against acute influenza virus infection

Abstract: Peptide-based T cell vaccines targeting the conserved epitopes of influenza virus can provide cross-protection against distantly related strains, but they are generally not immunogenic. Foreign antigen-specific regulatory T (Treg) cells are induced under subimmunogenic conditions peripherally, although their development and role in vaccine-mediated antiviral immunity is unclear. Here, we demonstrated primary vaccination with peptides alone significantly induced antigen-specific Foxp3 Treg cells, which were fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 39 publications
0
38
0
Order By: Relevance
“…Our study model resembles a preventative vaccination scenario in which an antigen‐specific mTreg pool was established before the host was IAV infected. IAV‐specific mTregs can be induced after vaccination with UV‐inactivated IAV or vaccines containing specific IAV peptides, although such Tregs may dampen the effector T‐cell response a little . It is possible and likely helpful that for future IAV vaccines to incorporate specific strategies to stimulate some IAV‐specific mTregs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study model resembles a preventative vaccination scenario in which an antigen‐specific mTreg pool was established before the host was IAV infected. IAV‐specific mTregs can be induced after vaccination with UV‐inactivated IAV or vaccines containing specific IAV peptides, although such Tregs may dampen the effector T‐cell response a little . It is possible and likely helpful that for future IAV vaccines to incorporate specific strategies to stimulate some IAV‐specific mTregs.…”
Section: Discussionmentioning
confidence: 99%
“…IAV-specific mTregs can be induced after vaccination with UV-inactivated IAV or vaccines containing specific IAV peptides, although such Tregs may dampen the effector T-cell response a little. 38,39 It is possible and likely helpful that for future IAV vaccines to incorporate specific strategies to stimulate some IAV-specific mTregs. It would be more appealing if such vaccine is given via the intranasal route and induces lung-resident mTregs as intranasal administration but not injection of influenza vaccines are more expected to improve the efficacy of influenza vaccines and generating lung-resident memory T cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, functionally active and virus‐specific FOXP3 + Tregs were induced inhepatitis C virus infection and can provide targeted immune regulation in vivo . It was also reported that the induction of Tregs upon vaccination sometimes attenuates the immunity induced by the vaccine . Interestingly, higher frequency of CD4 + CD25 high Treg cells was detected in some hemophilia patients with FVIII inhibitors, suggesting generation of potential FVIII‐specific Tregs.…”
Section: Discussionmentioning
confidence: 96%
“…In the response to the HBV vaccine, a peptide antigen administered intramuscularly, the helper CD4 T-cell function plays a major role [13, 14] and it is well assumed that T-cell exhaustion and senescence related to HIV infection may result in the failure of such response [15]. The involvement of Treg cells in several immunization models is also being studied [16, 17, 18]. The rationale is that Treg cells suppress the proliferation and cytokine secretion of CD4, CD8 T cells and monocytes, dendritic and B cells [19, 20].…”
Section: Discussionmentioning
confidence: 99%